Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) Ubiquitylation as a Novel Pharmaceutical Target for Cystic Fibrosis - Ryosuke Fukuda; Tsukasa Okiyoneda (MDPI AG, 2020)
Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene decrease the structural stability and function of the CFTR protein, resulting in cystic fibrosis. Recently, the effect of CFTR-targeting combination therapy has dramatically increased, and it is expected that add-on drugs that modulate the CFTR surrounding environment will further enhance their effectiveness. Various interacting proteins have been implicated in the structural stability of CFTR and, among them, molecules involved in CFTR ubiquitylation are promising therapeutic targets as regulators of CFTR degradation. This review focuses on the ubiquitylation mechanism that contributes to the stability of mutant CFTR at the endoplasmic reticulum (ER) and post-ER compartments and discusses the possibility as a pharmacological target for cystic fibrosis (CF).